The role of associations in regional innovation systems - Knut Koschatzky; Esther Schnabl; Andrea Zenker; Thomas Stahlecker; Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
This paper addressed the need for research regarding the role of associations in innovation systems. As defined here, the term association embraces not only organisations like business associations, but all actors who associate to pursue joint objectives and positively influence their (regional) innovation system. In the innovation system's perspective, these associations perform intermediary functions. As the relevant activities are often initiated by individuals acting in specific environments and circumstances, we need to consider not only the level of the organisation (i.e. meso level), but also the macro level of the innovation system and the micro level of individuals. Against the background of economic and social theory, intrinsic motivations have therefore also been discussed. External conditions, like the mode of governance and the logic of influence are also relevant as these define the framework conditions. Over time, associations may evolve in line with changes in the environment and internal developments. This evolution can be regarded as a life cycle which is specific to each association. Different types of associations and their specific functions have been mentioned using the example of Germany. While each of the listed associations can be regarded as an individual case, we can also assume that there are certain traits which are shared by all of them. Thus, we proposed four hypotheses addressing the macro level, i.e. the level of the regional innovation system, the meso level, i.e. the level of the association, and the micro level, which considers the motivations of individuals. We further proposed an empirical concept to be applied to study the role of associations in innovation systems.
urn:nbn:de:0011-n-2869598
Keywords: 330